CARGO SECURING IN SELECTED VEHICLES AND TRANSPORT OF EXPLOSIVES (Perner's Contacts, 2017)
The article deals with evaluation of transport experiments to compare selected vehicles in the context of inertial forces effect on cargo during transport. Emphasis is placed on the adequacy of the cargo securing in terms of the size of inertia forces (acceleration coefficients) that can represent a safety risk not only for the cargo, vehicle or crew of the vehicle, but also for other drivers (road users). In a separate part of the article, aspects of the transport of explosives are analyzed taking into account the sizes of inertia forces during transport. Paper also includes analysis of differences in transport of industrial explosives and military transport of explosives.
Keywords: cargo securing; transport; inertial forces; acceleration coefficients; transport of explosives; sensitivity